The 35-mm rule to guide pneumothorax management: Increases appropriate observation and decreases unnecessary chest tubes. Issue 6 (4th June 2022) - Figueroa, Juan F.; Karam, Basil S.; Gomez, Jose; Milia, David; Morris, Rachel S.; Dodgion, Christopher; Carver, Thomas; Murphy, Patrick; Elegbede, Anuoluwapo; Schroeder, Mary; de Moya, Marc A.
Abstract : INTRODUCTION: Axial imaging has allowed for more precise measurement and, in-turn, more objective guidelines related to the management of traumatic pneumothoraces (PTXs). In 2017, our trauma center used a guideline to observe any PTX ≤35 mm in stable patients. We hypothesize that this guideline would decrease unnecessary chest tubes without affecting failure rates. METHODS: This is a single-center retrospective review of all adult trauma patients who had a PTX diagnosed on computed tomography before (2015–2016) and after (2018–2019) guideline implementation. We excluded patients with chest tubes inserted before computed tomography, concurrent hemothoraces, mechanical ventilation, or mortality in the first 24 hours. Descriptive statistical analyses, χ2 test, and Mann-Whitney U test were performed as appropriate. RESULTS: A total of 266 patients met our inclusion criteria. Ninety-nine (37.2%) and 167 patients (62.7%) were admitted before and after 2017, respectively. Overall, there were no differences in demographics or severity of injuries between both groups. After guideline implementation, there was a significant increase in observation rates and compliance rate. Tube thoracostomies decreased from 28.3% to 18% (p = 0.04). There were no statistically significant changes in observation failure rates, hospital or intensive care unit length of stay, complications, or mortality. CONCLUSION: The implementation of the 35 mm guideline is an effective tool to decrease unnecessary tube thoracostomy in hemodynamically normal patients without evidence of hemothorax. LEVEL OF EVIDENCE: Therapeutic/care management, level III. Abstract :